Determination of Specific Heat of Cloves using Differential Scanning Calorimetry - Singh, K K; Goswami, T K (Journal of Agricultural Engineering, 2006)
The knowledge of specific heat of cloves is useful to design cryogenic system for grinding and to simulate and model the heat transfer in the grinder. The paper reports measurement of specific heat of cloves at different moisture contents and temperatures using differential scanning calorimetry technique. The observed values of specific heat increased from 1932 to 2816 J/kgÂ°C with increase in temperature from -60 to 60Â°C and moisture content from 3.8 to 18.8% (d.b.). The specific heat followed linear relationship with moisture content and second order polynomial relationship with temperature.